Synthesis and Antibacterial Activity of Some Oximes, Semicarbazones and Thiosemicarbazones - Desai, M.J.; Desai, K.K. (Asian Journal of Chemistry, 2010)
A series of oximes, semicarbazones and thiosemicarbazones have been synthesized from 2,4-dihydroxyacetophenone; 2,4-hydroxy-5nitroacetophenone and 2,4-dihydroxy-5-bromoaceto-phenone and their antibacterial activity have been studied. The compounds have been characterised by elemental analysis and IR spectra.